Unraveling the Labor Absorption Paradox: The Mediating Role of Human Resource Quality on Hospitality Training and Skills - Erma Yanuarni; Qatrun Nada; Muhamad Johari; M. Setyo Nugroho (Jurnal Pariwisata Nusantara (JUWITA), 2026)
The rapid growth of the tourism sector in Central Lombok Regency has not been fully matched by optimal local labor absorption, due to constraints on human resource (HR) competency. This study aims to examine the effect of hospitality training and hospitality skills on labor absorption, with HR quality serving as a mediating variable. Using an explanatory quantitative approach, the study sample comprised hospitality workers in Central Lombok Regency, selected via stratified random sampling. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that hospitality skills have a positive and significant effect on HR quality and labor absorption. However, it was found that hospitality training does not have a significant direct effect on labor absorption. This finding confirms the existence of skill-based recruitment in the local hospitality industry, which prioritizes practical, ready-to-use skills over formal training certificates. Additionally, human resource quality was found to mediate the relationship between skills and labor absorption significantly, but failed to mediate the relationship between training and labor absorption. This study recommends aligning training curricula with industry standards to enhance the local workforce's competitiveness in the Mandalika Special Economic Zone. Keywords: Hospitality Training, Hospitality Skills, Human Resource Quality, Labor Absorption, Lombok Tourism.